Time course of cerebral oxygenation and cerebrovascular reactivity in Kyrgyz highlanders. A five-year prospective cohort study - Luyken, Matthias C.; Appenzeller, Paula; Scheiwiller, Philipp M.; Lichtblau, Mona; Mademilov, Maamed; Muratbekova, Aybermet; Sheraliev, Ulan; Abdraeva, Ainura; Marazhapov, Nuriddin; Sooronbaev, Talant M.; Ulrich, Silvia; Bloch, Konrad E.; et al. (Frontiers in Physiology, 2023)
Abbreviation list Bf Breathing frequency cHb Change in cerebral haemoglobin concentration COPD Chronic obstructive pulmonary disease CTO Cerebral tissue oxygenation FiO2 Fractional of inspired oxygen HAPH High-altitude pulmonary hypertension HR Heart rate mPAP Mean pulmonary artery pressure NIRS Near-infrared spectroscopy PaCO2 Arterial partial pressure of carbon dioxide PaO2 Arterial partial pressure of oxygen PetCO2 End-tidal partial pressure of carbon dioxide SaO2 Arterial oxygen saturation SpO2 Saturation of oxygen 1 Abstract 1.1 Introduction This prospective cohort study assessed the effects of chronic hypoxaemia due to high-altitude residency on the cerebral tissue oxygenation (CTO) and cerebrovascular reactivity. 1.2 Methods Highlanders, born, raised, and currently living above 2500m, without cardiopulmonary disease, participated in a prospective cohort study from 2012 until 2017. The measurements were performed at 3250m. After 20 min of rest in supine position while breathing ambient air (FiO2 0.21) or oxygen (FiO2 1.0) in random order, guided hyperventilation followed under the corresponding gas mixture. Finger pulse oximetry (SpO2) and cerebral near-infrared spectroscopy assessing CTO and change in cerebral haemoglobin concentration (cHb), a surrogate of cerebral blood volume changes and cerebrovascular reactivity, were applied. Arterial blood gases were obtained during ambient air breathing.Results 53 highlanders, aged 50±2y, participated in 2017 and 2012. While breathing air in 2017 vs. 2012, PaO2 was reduced, mean±SE, 7.40±0.13 vs. 7.84±0.13kPa; heart rate was increased 77±1 vs. 70±1bpm (P<0.05) but CTO remained unchanged, 67.2±0.7 vs. 67.4±0.7%. With oxygen, SpO2 and CTO increased similarly in 2017 and 2012, by a mean (95%CI) of 8.3% (7.5-9.1) vs. 8.5% (7.7-9.3) in SpO2, and 5.5% (4.1-7.0) vs. 4.5% (3.0-6.0) in CTO, respectively. Hyperventilation resulted in less reduction of cHb in 2017 vs. 2012, mean difference (95%CI) in change with air 2.0 U/L (0.3-3.6); with oxygen, 2.1 U/L (0.5-3.7).Conclusions Within 5 years, CTO in highlanders was preserved despite a decreased PaO2. As this was associated with a reduced response of cerebral blood volume to hypocapnia, adaptation of cerebrovascular reactivity might have occurred.